2021
DOI: 10.1016/j.celrep.2021.108894
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic shifts in cellular fate are linked to proteotype changes in lineage-biased hematopoietic progenitor cells

Abstract: Highlights d >4,000 proteins quantified in fetal and adult hematopoietic progenitor cells (HPCs) d Protein expression in HPCs separates cells based on ontogenic stage and lineage potential d Generic fetal features are suppressed in myeloid-restricted progenitors d Low Irf8 expression partially drives an impairment in monopoiesis in fetal HPCs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
2
10
0
Order By: Relevance
“…Some innate immune cells (e.g., peritoneal B1 B cells and gd T cells) arise almost exclusively from fetal HSCs [16−19]. Phenotypic MPP and HPC subpopulations also have distinct lineage outputs during fetal and adult stages [20,21]. These observations suggest that hematopoietic progenitors must undergo considerable transcriptional and epigenetic reprogramming between birth and adulthood.…”
mentioning
confidence: 99%
“…Some innate immune cells (e.g., peritoneal B1 B cells and gd T cells) arise almost exclusively from fetal HSCs [16−19]. Phenotypic MPP and HPC subpopulations also have distinct lineage outputs during fetal and adult stages [20,21]. These observations suggest that hematopoietic progenitors must undergo considerable transcriptional and epigenetic reprogramming between birth and adulthood.…”
mentioning
confidence: 99%
“…Irf8 is a highly important regulator of lineage choices between neutrophils, monocytes and dendritic cells (DCs), and represents an example of a TF driving lineage commitment in a dose-dependent manner; lack of this TF promotes neutrophil generation whereas low and high levels drive differentiation towards inflammatory Ly6C + monocytes and DCs, respectively ( Murakami et al, 2021 ). In line with this, fetal granulocyte-monocyte progenitors (GMPs), which express low levels of Irf8 protein ( Jassinskaja et al, 2021 ), have limited potential to produce fully mature inflammatory monocytes compared to adult GMPs. Intriguingly, a recent study comparing human FL and fetal bone marrow hematopoiesis revealed that myeloid potential is remarkably low in the former relative to the latter ( Popescu et al, 2019 ; Jardine et al, 2021 ), further highlighting the differential lineage bias of HSPCs derived from different stages of ontogeny.…”
Section: Intra- and Extracellular Regulation Of Hematopoiesismentioning
confidence: 98%
“…While myeloid potential is nearly completely lost at the CLP stage of lymphopoiesis in vivo , myeloid programs have been shown to be partially reactivated during ex vivo culture of adult CLPs under lymphomyeloid differentiation conditions ( Richie Ehrlich et al, 2011 ). We have recently shown that this is not the case for fetal CLPs, which retain lymphoid restriction in the presence of myelopoiesis-promoting cytokines in culture, and, accordingly, express lower levels of proteins associated with myelopoiesis than their adult counterparts ( Jassinskaja et al, 2021 ).…”
Section: Intra- and Extracellular Regulation Of Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…It should finally be noted that fetal and adult HSPCs demonstrate significant differences in several key functional aspects such as cell cycle kinetics [29][30][31], response to inflammatory stress, and the production of various subpopulations of blood and immune cells [32].…”
Section: Development Of Hematopoiesis In Embryo 1hematopoietic Cells During Embryogenesismentioning
confidence: 99%